Adapting 2D positional control methodologies based on linear elements to 3D. Issue 342 (May 2015) - Mozas-Calvache, A. T.; Ariza-López, F. J.
<x content-type="archive" xml:space="preserve">Abstract</x> In this study we describe the adaptation of several 2D positional control methodologies based on linear elements to 3D. The selected methods have been used previously in several studies for controlling different kinds of lines and cartographic products, but always in a planimetric way. This study analyses the consequences of the inclusion of the heights in these methods by adapting the processes of calculation to the Z component. The methods to be adapted have been selected from the literature and are related to those based on calculations of distances and areas. The proposed methodology is applied to a real case, more concretely to a road extracted from two official databases in Spain, in order to check it and as a preliminary test for performing future 3D positional controls using these methods.